Strengthening collaborative teaching as a strategy to improve reading comprehension - Núñez Palma, Mauricio; Bustos Fajardo, Heidy; Matus Morales, Gabriela; Fuentes Núñez, Julieta (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
The objective of this research is to explore how Professional Learning Communities (PLCs) and curriculum coreization can strengthen collaborative work among teachers and contribute to addressing low reading comprehension in a school in the Lo Espejo district, where 89.1% of students demonstrate “insufficient” or “basic” reading levels. A qualitative study was conducted using a phenomenological ethnographic approach. Eight members of the educational community (teachers and administrators) participated. Through observations, document analysis, and interviews, the study sought to understand the teachers’ lived experience with collaborative processes and curriculum innovation. The findings reveal a deeply ingrained culture of professional isolation, described by teachers as “working like an island.” The implementation of PLCs and curriculum coreization acted as a turning point. These strategies fostered a shift from initial moments of tension and mistrust toward practices of interdependence, interdisciplinary dialogue, and joint planning around Socially Relevant Problems. Collaborative work does not emerge spontaneously: it requires formal structures, a shared pedagogical purpose, and key institutional conditions, especially dedicated time. Curriculum integration allowed for a redefinition of reading comprehension as a collective responsibility, strengthening teachers’ identity as “curriculum producers.” Although its prospective nature limits generalizability, the study offers a profound insight into teacher professional development and suggests the need for longitudinal research.